A Leadership Perspective on the Plastic and Reconstructive Surgery Residency Application Cycle During the COVID-19 Pandemic. (December 2022) - Jain, Abhishek; Brown, Geoffrey; Hudson, H. Todd; Patel, Ashish; Herrera, Fernando A.
Abstract: Introduction: The purpose of this study was to identify leadership perspective on the impact of COVID-19 Plastic and Reconstructive Surgery (PRS) residency application cycle in 2020 and its future implications. Methods: A survey was sent to residency program leaders (RPL), consisting of program directors and division chiefs/chairs. The survey was sent weekly for 4 weeks and remained open for 28 days. Results: A total of 156 PRS RPL were emailed. Response rate was 24% (38/156). A total of 68% were division chiefs/chairs, and 42% were program directors. Ten percent were both division chiefs/chairs and program directors. Among them, 78% were male. Eighty-seven percent of RPLs reported changes in the number of away rotations, of which 91% reported less away rotations. Only 27% of programs provided virtual away rotations (VAR), and 88% of RPLs were not comfortable writing letters of recommendation after VARs. Hundred percent of cases reported that VARs influenced whether an applicant received an interview. A total of 24 RPLs (63%) reported no changes in how they viewed applications due to the pandemic. However, 5 (13%) reported USMLE scores were more important, 4 (11%) reported research was more important, and 4 (11%) reported LORs were more important. Sixty-six percent did not feel they relied heavily on home institution candidates. Seventy-six percent found virtual interviews to be effective in evaluating applicants, and 71% reported they would add virtual interviews in future interviews. Conclusions: During the 2020-2021 PRS residency application cycle, fewer away rotations were offered, and formerly in-person activities were moved to virtual platforms. Virtual activities caused difficulty assessing candidates for many residency programs.